Dr. Fauci : how a boy from Brooklyn became America's doctor - Messner, Kate (Simon & Schuster Books for Young Readers, 2021)
"Before he was Dr. Fauci, director of the National Institute of Allergy and Infectious Diseases, Anthony Fauci was a curious boy in Brooklyn, delivering prescriptions from his father's pharmacy on his blue Schwinn bicycle. His father and immigrant grandfather taught Anthony to ask questions, consider all the data, and never give up--and Anthony's ability to stay curious and to communicate with people would serve him his entire life. This engaging narrative, which draws from interviews the author did with Dr. Fauci himself, follows Anthony from his Brooklyn beginnings through medical school and his challenging role working with seven US presidents to tackle some of the biggest public health challenges of the past fifty years, including the COVID-19 pandemic. Extensive backmatter rounds out Dr. Fauci's story with a timeline, recommended reading, a full spread of facts about vaccines and how they work, and Dr. Fauci's own tips for future scientists"--